Environmental learning in a virtual environment: Do gender, spatial self-efficacy, and visuospatial abilities matter?. (December 2021) - Miola, Laura; Meneghetti, Chiara; Toffalini, Enrico; Pazzaglia, Francesca
Abstract: The study investigated the role of individual differences in environmental learning, including gender, visuospatial cognitive abilities, and spatial self-efficacy. A sample of 173 participants learned a route in a virtual environment and, afterwards, indicated the starting point (pointing task) and located landmarks on a sketch map (map-completion task). An ad hoc single-item question measured the specific spatial self-efficacy referring to the tasks, whereas we assessed global spatial self-efficacy and visuospatial cognitive abilities using a questionnaire and two tasks, respectively. The results of the structural equation modelling (SEM) showed that general and task-specific self-efficacy and visuospatial cognitive abilities mediated the relationship between gender and map-completion. These findings suggest that self-efficacy (general and task-specific) and visuospatial cognitive abilities have a role in explaining the relationship between gender and environmental learning. Highlights: Global and task-specific spatial self-efficacy influence mental representations. Self-efficacy mediates the relation between gender and spatial learning. Visuospatial abilities mediate the relation between gender and spatial learning.